Ethno-religious identity as a factor of tolerance among the students of Almaty - Tutinova, Nurgul; Tussupbekov, Zharkyn; Meyrbaev, Bekzhan; Kartashov, Kirill; Otaraliyeva, Gulshat (Opción, 2019)
The article deals with the peculiarities of national and religious self-identification of the Kazakh Almaty student youth as part of the titular nation via general scientific methods of knowledge with the use of sociological approach, research methods, and analysis. As a result, Ethnoreligious self-consciousness of the majority of young people is alien to any expressed nationalist aspirations. In conclusion, increasing the ability of the state to influence the situation in the country in a desirable way requires rapid involvement (in the system mode) of regulatory mechanisms.